Innovative Potential Implementation of Public Procurement in Russia - N. G. Sirotkina (Управленческие науки, 2017)
Public procurement is widely used for encouraging the innovative activity in developed countries, meanwhile in Russia innovative procurement is not used systematically which updates the urgency of the research. The systematization of innovative activity stimulation mechanisms in the domestic system of public procurements is performed in the article. The analysis of these mechanisms’ practice of using allowed revealing a large number of the barriers which do not allow using the possibilities of the state order in forming the demand for innovative products. Such barriers are the drastic antimonopoly and anti-corruption norms interfering to use the flexible specifications and qualitative criteria for applications evaluation, the limited usage of “life-cycle cost” criterion, and also the absence of need’s long-term planning in the domestic public procurement system for innovative production. The result of the research is a conclusion about the need of transition from fragmentary measures of innovations support to strategy development of encouraging the demand for innovations, and not only in system of public procurements, but also in the sphere of the companies purchases with the state participation and infrastructure monopolies.